General Health Status of Adolescent Girls of Different Income Ranges: Exploring the Health Status of Adolescent Girls in Different Income Ranges (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Health status of adolescent girls is a very important aspect. This Paper deals with this important aspect and has conducted an extensive study in this area in district Kurukshetra with the help of a questionnaire based survey followed by personal interaction with them as well as their families.